Inheritance of low-level resistance to penicillin, tetracycline, and chloramphenicol in Neisseria gonorrhoeae. - Sparling, P F (1975)
The genetics of low-level resistance to penicillin and other antibiotics in a clinical isolate and a multistep laboratory mutant of Neisseria gonorrhoea was studied by transformation. Mutations at three loci affected sensitivity to penicillin. Mutation at penA resulted in an eightfold increase in resistance to penicillin without affecting response to other antimicrobial agents. Mutation at ery resulted in a two- to fourfold increase in resistance to penicillin and similar increases in resistance to many other antibiotics, dyes, and detergents. Mutation at penB resulted in a fourfold increase in resistance to penicillin and tetracycline, the phenotypic expression of which was dependent on the presence of mutation at ery. The cumulative effect of mutations at penA, ery, and penB was an approximate 128-fold increase in penicillin resistance, to a minimum inhibitory concentration of 1.0 mug/ml. Low-level resistance to tetracycline or chloramphenicol was due to similar additive effects between mutations at the nonspecific ery and penB loci and a locus specific for resistance to each drug (tet and chl, respectively). No evidence was found for penicillinases or other drug-inactivating enzymes.